Melt with you - Dugan, Jennifer (G.P. Putnam's Sons, 2022)
Fallon and Chloe are as different as can be, but they've been best friends forever. That is until they hooked up right before Chloe left for college, and now they haven't spoken in a year. Chloe's returned home from school, and it's impossible for Fallon to avoid her as their moms own a gourmet ice cream truck together where the girls both work. When their moms are called away for an important meeting with potential investors, the two embark on a cross-country road trip for a series of food truck festivals, and they are forced to have an honest conversation about their feelings.